MHC class I regulation in response to dsRNA stress. (October 2022) - Sznarkowska, Alicja; Mikac, Sara; Fahraeus, Robin
Abstract : Downregulation of surface MHC class I molecules is a common phenomenon in cancer but underlying mechanisms are undefined. The nuclear factor erythroid 2 related factor 2 (Nrf2) is a relevant basic leucine zipper (bZIP) transcription factor that is essential in the regulation of cell cycle homeostasis, cytoprotection, and innate immunity when cells are under stressful conditions. Nrf2 was shown to protect cells against multiple redox-induced and xenobiotic-induced diseases including cancer and its activation is beneficial in terms of prevention of chronic diseases. Toll-Like Receptor (TLR) signaling, crucial for innate immune response, induces Nrf2 pathway. Here we show that dsRNA (which mimic viral infection) activates Nrf2 pathway and induces MHC class I levels in normal lung fibroblasts (NLF) but not in NSCL cancer cell lines A549 and RERF LC. Depletion of Nrf2 decreased MHC class I levels in NLF but not in cancer cell lines. We speculate that dsRNA activates Nrf2 pathway to induce MHC class I expression in non-transformed cells which allows for coordinating innate and adaptive immune response. This regulation is lost in cancer.